PENEGAKAN HUKUM TERHADAP PENGENDARA KENDARAAN BERMOTOR ANAK - Susanti, Susi; Fahmi; Harahap, Irawan (Collegium Studiosum Journal, 2024)
Traffic law enforcement is one of the important components in maintaining safety and order on the road. In Indonesia, traffic regulations are governed by Law Number 22 of 2009 concerning Road Traffic and Transportation (UU LLAJ). This phenomenon not only endangers the safety of the children riders themselves but also other road users. Law No. 22 of 2009 concerning Road Traffic and Transportation provides a legal basis to regulate this phenomenon to create order, security, and safety in traffic. The method used is sociological legal research. Based on the research findings, it is known that the regulation on the ownership of a driver's license (SIM) for child motor vehicle riders is regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation. The requirement for someone to have a driver's license is to be 17 (seventeen) years old for SIM A, C, and D, while 20 years old for SIM B1, and 21 years old for SIM B II. The regulation regarding the ownership of a driver's license (SIM) for child motor vehicle riders is an important preventive measure to ensure safety on the road. Law enforcement against child motor vehicle riders in the jurisdiction of Polresta Pekanbaru is still faced with the issue of motor vehicles being ridden by children, which could trigger traffic accidents. Efforts to address this have been implemented through various measures, including traffic raids and vehicle administrative checks.